PENGARUH SELF ASSESSMENT SYSTEM, PEMERIKSAAN PAJAK DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PPN DI KOTA BEKASI SELATAN - Fanny Panjaitan; Paul Eduard Sudjiman (Jurnal Ekonomis, 2021)
This study has a goal, namely how the effect of the self-assessment system and tax bills on the value added tax receipts of the city of Bekasi respondents in this journal the sample is all taxpayers for themselves as well as corporate taxpayers in the city of South Bekasi. The data collection technique for this research is the documentation method where the technique for collecting data is made by collecting all secondary data and all the information contained in the document is also included for problem solving. Data analysis was assisted by simple linear regression through the t test. This finding resulted in data where the self-assessment system, as well as tax collection as a whole, had an effect on value added tax receipts at the Cibitung mayor's office for 2019-2020.